Urodynamic Pressure-Flow Study (Pfs) for the Prediction of Surgical Outcome in Bph With Urinary Retention (Bangladesh Journal of Urology, 2020)
Introduction: Urinary retention can be either chronic or acute in onset. Urinary retention can result from impaired detrusor contractility or obstruction of bladder outlet. Twenty five to 30% of men with decreased flow are not obstructed 1. Either uroflowmetry or post-void residue (PVR) can not differentiate obstruction from impaired detrusor contractility. In this study, an effort has been paid to know the usefulness of pressure-flow study in urinary retention due to suspected benign prostatic hyperplasia(BPH) cases for predicting the outcome of surgery.Methods: This is a before after clinical study, conducted in Bangabandhu Sheikh Mujib Medical University, Dhaka. Total 32 patients were selected for the study. Patients age ranges from 49-78 years.Patients with chronic and refractory urinary retention due to BPH were enrolled for the study. They were divided into group A (pre-operative) and group B (Post-operative). TURP was done in all 32 patients by single surgeon. Study variables were detrusor pressure at maximum flow (Pdet@Qmax), bladder outlet obstruction index(BOOI), bladder contractility index( BCI) and post void residue (PVR).Result: Total number of patients was 32. Age ranges from 49-78 years. Twenty one (65.6%) had BPH with chronic retention and 11 (34.4%) had BPH with refractory retention.Pdet@Qmax between Group A and Group B was highly significant (p=0.001). But difference is not significant in Pdet@Qmax d” 40 subgroup of patients (p=0.673). Bladder outlet obstruction index between Group A and Group B is highly significantly (p=0.001), but, that does not observed in BOOI 150 ) subgroups are significant ( p=0.001 and 0.001 respectively ). But it is not significant in BCI300m subgroup, difference is insignificant (p=0.120).Conclusion: In this study, overall favorable outcome observed in all patients after TURP but Pdet@Qmax